Expression of Anti-Toxoplasma scFv Antibodies in Plants / Go Pei See - Go, Pei See (2013)
Toxoplasmosis is a disease caused by a single-celled protozoan parasite known as Toxoplasma gondii. It infects approximately one-third of the world’s population. The definitive hosts of this obligate intercellular parasite are feline family members; but it is widespread in human and many warm-blooded animals, particularly farm animals. The disease causes critical symptoms in infants, pregnant women, and fetuses and there is still an urgent need new more effective therapeutic, diagnostic and bioimaging compounds as well as affordable production methods amenable to upscaling. A plant-based recombinant antibody against Toxoplasma antigen may offer a potential approach in developing strategies to produce such molecules. The antibody was designed to specifically target surface protein of the T.godii tachyzoites can be further developed as targeting antibodies or diagnostic reagents against the organism. Thus, in this study, anti-Toxoplasma scFv antibody genes were introduced into the pCambia1304 vector and transformed into Musa acuminata cv. Berangan and Nicotiana tabacum L. cv. SR1 leaf discs through Agrobacterium-mediated transformation. In addition, a KDEL retention sequence and Bowman-birk Serine proteinase inhibitor genes were added into the construct to stabilize and enhance the scFv antibody production. The transgene was successfully integrated into the tobacco genome. Unfortunately, the desired gene failed to integrate into banana genome despite many attempts and the possible constrains are discussed. Molecular analysis including PCR and Real-time PCR were used to confirm the integration of transgene into the plant genome. From Real-time PCR results, the average mRNA level for the leaves transformed with the construct pToxo130BBI based on the RT-qPCR of three transgenes elements was 4.4 fold when compared to non-transformed tobacco whereas for the construct pToxo130BBIKDEL, it was 3.58 fold higher. The unexpected lower level of mRNA for pToxo130BBIKDEL compared to III pToxo130BBI (0.82 fold) in Real-time PCR may not reflect the actual protein accumulation level in plant cell. Further studies need to be carried out to examine the effectiveness of adding KDEL retention sequence and Bowman-birk Serine proteinase inhibitor genes in the constructs through quantitative analysis of the tobacco-expressed protein. Overall, the study proposes a potentially useful expression platform for production of anti-Toxoplasma scFv antibodies.